Cement admixture, expanding material and cement composition
By adjusting the mass ratio of sulfur-aluminum calcium and sulfur-aluminum calcium calcium silicate in cement external dopants, and combining the use of free lime, anhydrous gypsum and other components, the problem of poor performance of fluidity and initial strength at high temperatures is solved, and good flow retention and excellent initial strength under high temperature conditions are achieved.
Patent Information
- Application Number
- CN202510123876.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-23
- Filing Date
- 2021-04-22
- Publication Date
- 2025-04-15
AI Technical Summary
It is difficult for existing expanded materials to maintain good fluidity and initial strength performance at high temperatures.
By adjusting the mass ratio of sulfhydryl and sulfhydryl in the cement external dopant, ensure that the ratio of sulfhydryl/sulfhydrylyl is between 0.5 and 40, and the combination of free lime, anhydrous gypsum and other components are used.
The cement external dopant has good flow retention and excellent initial strength performance under high temperature conditions, and is suitable for use as an expanded material.
Smart Images

Figure BDA0005259510050000071 
Figure BDA0005259510050000091 
Figure BDA0005259510050000111
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 202180029239.X, application date April 22, 2021, and invention name “Cement admixtures, expansive materials and cement compositions”. Technical Field
[0002] The present invention relates to a cement admixture, an expanding material and a cement composition used, for example, in the field of civil engineering and construction. Background Art
[0003] Reducing cracks in cement and concrete is important from the viewpoints of reliability, durability, and aesthetics of concrete structures, and further development of the technology of cement admixtures, that is, cement-based expansive materials, which have the effect of improving these cracks is desired.
[0004] So far, there have been proposed concrete expansion materials having excellent expansion characteristics with a small amount of addition (Patent Document 1), cement expansion materials with the surface of free lime covered with calcium carbonate (Patent Document 2), etc. In addition, in recent years, the combined use of expansion materials and shrinkage reducing agents has been proposed (Patent Document 3).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent No. 4244261
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 54-93020
[0009] Patent Document 3: Japanese Patent Application Publication No. 2003-12352 Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, conventional expansion materials may have difficulty in obtaining good fluidity retention at high temperatures (30° C. or higher) or difficulty in obtaining excellent initial strength development.
[0012] In summary, an object of the present invention is to provide a cement admixture suitable as an expansion material that has good fluidity retention even at high temperatures and can also exhibit excellent initial strength performance.
[0013] Methods for solving problems
[0014] As a result of intensive research in view of the above-mentioned problem, the present inventors have found that the problem can be solved by setting the mass ratio of ye'elimite to ternesite (ye'elimite / ternesite) in a cement admixture of a specific composition to a predetermined range, thereby completing the present invention. That is, the present invention is as follows.
[0015] [1] A cement admixture comprising free lime, anhydrous gypsum, calcium sulfoaluminate and calcium sulfowellsite, wherein the mass ratio of calcium sulfoaluminate to the calcium sulfowellsite (calcium sulfoaluminate / calcium sulfowellsite) is 0.5 to 40.
[0016] [2] The cement admixture according to [1], comprising 20 to 80% by mass of the free lime.
[0017] [3] The cement admixture according to [1] or [2], wherein the total mass ratio of the free lime and the anhydrous gypsum to the calcite ((free lime+anhydrous gypsum) / calcite) is 20 to 90.
[0018] [4] An expansive material comprising the cement admixture according to any one of [1] to [3].
[0019] [5] A cement composition comprising the cement admixture according to any one of [1] to [3].
[0020] Effects of the Invention
[0021] According to the present invention, it is possible to provide a cement admixture suitable as an expansion material which has good fluidity retention even at high temperatures and can also exhibit excellent initial strength development. DETAILED DESCRIPTION
[0022] Hereinafter, the cement admixture, the expansion material, and the cement composition according to the embodiment of the present invention will be described. It should be noted that the parts and % used in the present specification are by mass unless otherwise specified.
[0023] [1. Cement admixtures and expansion materials]
[0024] The cement admixture of the present embodiment includes free lime, anhydrous gypsum, calcite and calcite.
[0025] (Calcium Sulfate Aluminum Oxide)
[0026] The calcium sulfoaluminate of the present embodiment is represented by 3CaO·3Al2O3·CaSO4 and has the same properties as hauynite (Ca2Na6Al6SiO6O 24(SO4)2) A mineral with a similar structure. It hydrates in the presence of gypsum and the like to form ettringite (3CaO·Al2O3·3CaSO4·32H2O), which helps to improve initial strength.
[0027] From the viewpoint of reactivity, the particle size of sulphoaluminite is preferably 4,500 to 12,000 cm in terms of Blaine specific surface area. 2 / g, more preferably 5,000 to 10,000 cm 2 / g.
[0028] The content of calcium sulfoaluminite is preferably 5 to 30 parts, more preferably 8 to 25 parts, based on 100 parts of the cement admixture. By setting the content to 5 to 30 parts, the initial strength can be improved.
[0029] (Calcium Sulfate Calcium Silica)
[0030] Sulfolatonite is a mineral represented by 5CaO·2SiO2·SO3, and promotes the hydraulic reaction of sulfolatonite. In addition, since sulfolatonite itself hardly reacts, it is presumed to play a role like a filler, which makes the fluidity retention good. Therefore, the slump loss can be reduced even at high temperatures.
[0031] The content of sulfoaluminite is preferably 1 to 20 parts, more preferably 3 to 18 parts, and even more preferably 5 to 15 parts per 100 parts of cement admixture. By setting the content to 1 to 20 parts, the hardening of sulfoaluminite can be accelerated and the fluidity can be kept good at the same time.
[0032] Here, the mass ratio of sulfoaluminite to sulfowellite (sulfoaluminite / sulfowellite) is 0.5 to 40, preferably 4 to 40, more preferably 6 to 30, and further preferably 8 to 25. If the mass ratio is less than 0.5, good expansion characteristics may not be obtained when applied to expansion materials, especially a large length change rate may not be obtained. In addition, if the mass ratio exceeds 40, it is difficult to obtain the hardening promotion effect of sulfoaluminite brought by sulfowellite.
[0033] (Free lime)
[0034] Free lime (f-CaO) is also called free calcium oxide. By including it in the cement admixture of the present embodiment, expansion characteristics are imparted, and as a result, drying shrinkage can be suppressed.
[0035] The free lime content is preferably 20 to 80 parts, more preferably 25 to 60 parts, based on 100 parts of the cement admixture. By containing 20 to 80 parts, the drying shrinkage can be inhibited without causing a decrease in long-term strength development.
[0036] During the firing process when preparing cement admixtures, the crystal particle size of free lime in the cement admixtures can be increased or the content can be increased by increasing the firing temperature or appropriately adjusting the amount and particle size of input raw materials other than the CaO raw material.
[0037] (Anhydrous gypsum)
[0038] The anhydrite of the present embodiment is not particularly limited, but it is preferable to use type II anhydrite, and among them, it is preferable to use acidic anhydrite having a pH of 4.5 or less.
[0039] Here, the pH of anhydrous gypsum refers to the pH of the supernatant obtained when 1 g of anhydrous gypsum is added to 100 mL of pure water and stirred.
[0040] From the viewpoint of initial strength development, the particle size of gypsum is preferably 2,000 cm in terms of Blaine specific surface area. 2 / g or more, more preferably 3,000 to 6,000 cm 2 In addition, the Blaine specific surface area value in this specification can be calculated|required based on JIS R5201 (physical test method of cement).
[0041] The content of gypsum is preferably 3 to 50 parts, more preferably 10 to 40 parts, based on 100 parts of the cement admixture.
[0042] In addition, when the content of gypsum in the cement admixture is small, gypsum may be additionally added in an amount ranging from 3 to 50 parts with respect to 100 parts of the cement admixture.
[0043] The mass ratio of the total of free lime and gypsum to calcite ((free lime+gypsum) / calcite) is preferably 20 to 90, more preferably 30 to 70. By setting the mass ratio to 20 to 90, good expansion characteristics due to free lime and gypsum can be easily obtained.
[0044] The cement admixture of the present embodiment preferably has a Blaine specific surface area of 2,000 to 6,000 cm 2 / g, more preferably 2,500 to 5,000. By making the Blaine specific surface area 2,000 to 6,000 cm 2 / g, it is possible to prevent the concrete structure from being destroyed due to long-term expansion when used as an expansive material, and it is possible to maintain good expansive performance.
[0045] The cement admixture of the present invention is obtained by appropriately mixing and calcining a CaO raw material, an Al2O3 raw material, a SiO2 raw material, a CaSO4 raw material and the like.
[0046] As CaO raw materials, limestone and slaked lime can be mentioned; as Al2O3 raw materials, bauxite and aluminum slag ash can be mentioned; as SiO2 raw materials, silica can be mentioned; as CaSO4 raw materials, dihydrate gypsum, hemihydrate gypsum and anhydrous gypsum can be mentioned.
[0047] These raw materials may contain impurities, but there is no particular problem as long as the effect of the present invention is not impaired. Examples of impurities include MgO, TiO2, MnO, P2O5, Na2O, K2O, Li2O, sulfur, fluorine, chlorine, and the like.
[0048] The cement admixture can be produced by mixing the above raw materials so as to have a desired mineral composition and then firing the mixture. The raw materials may be appropriately pulverized before or after firing.
[0049] The firing method is not particularly limited, but firing is preferably performed using an electric furnace, a kiln, etc. at a temperature of 1,100 to 1,600° C., more preferably 1,200 to 1,500° C. If the temperature is lower than 1,100° C., the expansion performance is insufficient, and if the temperature exceeds 1,600° C., gypsum (particularly anhydrous gypsum) may decompose.
[0050] When pulverizing, it is preferred that the Blaine specific surface area be 2,000 to 6,000 cm 2 The / g method is carried out by a known method.
[0051] The mineral content in the cement admixture prepared as above can be confirmed by conventional analytical methods. For example, the generated minerals of the crushed sample can be confirmed by a powder X-ray diffraction device, and the data can be analyzed by the Rietveld method to quantify the minerals. In addition, the mineral amount can also be calculated based on the identification results of the chemical composition and powder X-ray diffraction. In the present embodiment, the mineral amount is preferably calculated based on the identification results of the chemical composition and powder X-ray diffraction.
[0052] It should be noted that the content of chemical components can be obtained by fluorescent X-ray.
[0053] The cement admixture of the present embodiment preferably contains particles in which free lime, gypsum, calcite and calcite exist in the same particle.
[0054] Whether free lime, gypsum, sulfoaluminite and sulfowellite exist in the same particle can be confirmed by electron microscopy, etc. Specifically, the cement admixture is embedded in a resin, surface treated with an argon ion beam, the structure of the particle cross section is observed, and elemental analysis is performed, thereby confirming whether free lime, gypsum, sulfoaluminite and sulfowellite exist in the same particle.
[0055] The cement admixture of the present embodiment as described above is preferably used as an expansion material, for example. That is, the expansion material of the present embodiment is composed of the cement admixture described above. Thus, it has good fluidity retention even at high temperatures, so workability becomes good, and also can exert excellent initial strength performance.
[0056] [2. Cement composition]
[0057] The cement composition of the present embodiment contains the above-mentioned cement admixture. Here, as cement used in the cement composition, various Portland cements such as ordinary, early strength, super early strength, low heat and medium heat, various mixed cements obtained by mixing blast furnace slag, fly ash or silicon dioxide in these Portland cements, filling cements obtained by mixing limestone powder or blast furnace slow cooling slag fine powder, and environmentally friendly cement (environmentally friendly cement) made from municipal garbage incineration ash or sewage sludge incineration ash as raw materials can be listed, and one or more of them can be used. In addition, the cement admixture can also be the expansion material of the present embodiment.
[0058] In this embodiment, in addition to cement, cement admixtures, fine aggregates such as sand, and coarse aggregates such as gravel, one or more of admixtures such as early strength agent, quick hardening agent, water reducer, AE water reducer, high performance water reducer, high performance AE water reducer, fluidizing agent, defoamer, thickener, rust inhibitor, antifreeze agent, shrinkage reducer, pour point depressant, hydration heat inhibitor, polymer emulsion, clay minerals such as bentonite, anion exchangers such as hydrotalcite, slag such as pulverized blast furnace slag powder, blast furnace slow cooling slag powder, limestone powder, siliceous powder, gypsum, calcium silicate, volcanic ash, etc. can also be used in the range that does not substantially hinder the purpose of the present invention. In addition, as an organic material, it can also be used in combination with fibrous substances such as vinylon fiber, acrylic fiber, and carbon fiber.
[0059] The usage amount (mixing amount) of cement admixture (or expansion material) varies according to the mixing of concrete, and therefore is not particularly limited. Generally, in 100 parts of cement composition containing cement and cement admixture (or expansion material), it is preferably 3 to 12 parts, and more preferably 4 to 7 parts. By being 3 parts or more, sufficient expansion performance can be obtained. In addition, by being 12 parts or less, it will not expand excessively, and expansion cracks in concrete can be prevented.
[0060] Example
[0061] "Experimental Example 1"
[0062] The CaO raw material, Al2O3 raw material, SiO2 raw material, and CaSO4 raw material were mixed and crushed into the mineral ratio shown in Table 1, and then calcined at 1,200°C to form a clinker, which was then crushed using a ball mill to a Blaine surface area of 3,000 cm 2 / g, used to make cement admixtures.
[0063] It should be noted that the mineral composition was determined by calculation based on the chemical composition determined by fluorescent X-rays and the identification results of powder X-ray diffraction.
[0064] Using this cement admixture, 10 parts of cement admixture were used in 100 parts of cement composition composed of cement and cement admixture, and mortar with water / cement composition ratio = 50% and cement composition / sand ratio = 1 / 3 (mass ratio) was prepared in a room at 20°C, and the length change rate, flow retention at high temperature and compressive strength were measured. The results are shown in Table 1.
[0065] (Materials used)
[0066] CaO raw material: limestone
[0067] Al2O3 raw material: bauxite
[0068] SiO2 raw material: silica
[0069] CaSO4 raw material: anhydrous gypsum
[0070] Sand: JIS standard sand
[0071] Cement: Ordinary Portland cement, commercially available
[0072] (Test method)
[0073] ·Compression strength: A test piece of 4×4×16 cm was prepared in accordance with JIS R5201, and the compression strength at 7 days (7d) and 28 days (28d) of age was measured.
[0074] Length change rate: Based on JIS A6202, the length change rate was measured at 7 days (7d) and 28 days (28d) of age.
[0075] Flow retention at high temperature: Mortar was mixed according to JIS R5201-2015 "Physical testing methods for cement", and the 15-point flow value immediately after mixing was measured. Then, the 15-point flow value was measured after standing for 60 minutes, and the ratio of the value after standing for 60 minutes to the value immediately after mixing was evaluated to measure the flow retention at 30°C.
[0076] [Table 1]
[0077]
[0078] "Experimental Example 2"
[0079] The CaO raw material, Al2O3 raw material, SiO2 raw material, and CaSO4 raw material were mixed and crushed into the mineral ratio shown in Table 2, and then calcined at 1,200°C to form a clinker, which was then crushed using a ball mill to a Blaine specific surface area of 3,000 cm 2 / g, used to make cement admixtures.
[0080] It should be noted that the mineral composition was determined by calculation based on the chemical composition determined by fluorescent X-rays and the identification results of powder X-ray diffraction.
[0081] Using this cement admixture, 7 parts of cement admixture were used in 100 parts of cement composition composed of cement and cement admixture, and mortar with water / cement composition ratio = 50% and cement composition / sand ratio = 1 / 3 (mass ratio) was prepared in a room at 20°C, and the length change rate, flow retention at high temperature and compressive strength were measured in the same manner as in Experimental Example 1. The results are shown in Table 2.
[0082] [Table 2]
[0083]
[0084] "Experimental Example 3"
[0085] The CaO raw material, Al2O3 raw material, SiO2 raw material, and CaSO4 raw material were mixed and crushed into the mineral ratio shown in Table 3, and then calcined at 1,200°C to form a clinker, which was then crushed using a ball mill to a Blaine surface area of 3,000 cm 2 / g, used to make cement admixtures.
[0086] It should be noted that the mineral composition was determined by calculation based on the chemical composition determined by fluorescent X-rays and the identification results of powder X-ray diffraction.
[0087] Using this cement admixture, 7 parts of cement admixture were used in 100 parts of cement composition composed of cement and cement admixture, and mortar with water / cement composition ratio = 50% and cement composition / sand ratio = 1 / 3 (mass ratio) was prepared in a room at 20°C, and the length change rate, flow retention at high temperature and compressive strength were measured in the same manner as in Experimental Example 1. The results are shown in Table 3.
[0088] [Table 3]
[0089]
[0090] Industrial Applicability
[0091] The cement admixture of the present invention can be widely used in the field of civil engineering and construction using concrete.
Claims
1. A cement admixture comprising free lime, anhydrous gypsum, calcium sulfoaluminate and calcium sulfowellite, wherein the mass ratio of the calcium sulfoaluminate to the calcium sulfowellite, i.e., calcium sulfoaluminate / calcium sulfowellite, is 0.5 to 40. 2 . The cement admixture according to claim 1 , comprising 20 to 80% by mass of the free lime.
3. The cement admixture according to claim 1 or 2, wherein: The mass ratio of the total amount of the free lime and the anhydrous gypsum to the calcite, that is, (free lime+anhydrous gypsum) / calcite is 20 to 90.
4. An expansive material, comprising the cement admixture according to any one of claims 1 to 3.
5. A cement composition comprising the cement admixture according to any one of claims 1 to 3.
Citation Information
Patent Citations
Lime containing particulate composition* cement composition containing same and method of making same
JP1979093020A
Cement additive and cement composition
JP2003012352A